PREPARASI DAN KARAKTERISASI KOMPOSIT SELULOSA BAKTERIAL – RUMPUT LAUT (Eucheuma cottonii) UNTUK APLIKASI BIOMEDIS - Febbi Rahmayuni; Edi Nasra; Ananda Putra (Departemen Kimia FMIPA UNP, 2016)
Composite bacterial cellulose - seaweed (BC-SW) was prepared by immersing the bacterial cellulose (BC) in seaweed extract (SW) for 1,2,3, and 4 days. Has researched the effect of immersion time on the physical and mechanical properties of the composite, the result showed that longer of immersion time decreases the water content, the higher the compressive strength, tensile strength and elasticity BC-SW composite. From the research done, the content of BC reached 99 156% while for BC-SW composite decreased water content of up to 98 585%. In the compressive strength test, the compressive strength of BC is 0292 MPa, while the BC-SW composite the compressive strength increased 2 times to 8 times stronger than BC. The value of physical and mechanical properties have not been suitable with the standards for the manufacture of cartilage. Analysis of the structure of KSB-RL was observed using FTIR and XRD. Results of FTIR spectra showed no new functional groups but only experienced a slight shift in the vibrational wave numbers.